Relasi Gagasan Seyyed Hosein Nashr Tentang Islamisasi Ilmu Pengetahuan Melalui Pendekatan Integrasi Agama dan Sains Terhadap Pendidikan Islam di Indonesia - Sigit Candra Nuraziz; Fauzi (Pascasarjana IAI Nasional Laa Roiba Bogor, 2025)
This study is intended to explore the concept of integrative education between religion and science and how the idea of Islamization of science can become one of the bases for improving the design of Islamic Education in Indonesia. The method used in this paper uses the library research method or approach, that library studies can be interpreted as a series of activities related to the method of collecting library data, reading and recording and processing research materials. The results of this study indicate that the relevance between religion and science is not always harmonious, as shown in this paper that the emergence of the issue of Islamization of science is a response to the dichotomy of science and religion that was introduced by the secular West and modern society culture into the Islamic world. The progress achieved by modern science has brought amazing influences, but on the one hand it has also had a negative impact to the point of giving rise to harsh criticism of the progress of science itself, because modern science is considered to have dried up or separated from Islamic religious values. The connection with the concept of integrative education is the idea of Islamization of science considering that so far science has been viewed as neutral, universal, and value-free. These problems are important to examine which are then found to be beneficial for the development of Islamic Education as stated in this paper.